Collaborative Governance dalam Kegiatan Pembinaan Kemandirian Perkebunan Guna Mendorong Keberhasilan Program Ketahanan Pangan di Lembaga Pemasyarakatan Narkotika Kelas IIA Bangli - Agastya, I Kadek Dwi Pramesthi; Simanjuntak, Meitisa Vanya (SENTRI: Jurnal Riset Ilmiah, 2025)
The Indonesian government is currently intensively promoting the national food security program, where correctional institutions (Lapas) play a strategic role through inmate self-reliance development programs. This study aims to analyze the implementation of collaborative governance in agricultural self-reliance programs at the Class IIA Bangli Narcotics Prison to support food security efforts. This research employs a descriptive qualitative method with data collected through observation, in-depth interviews, and documentation. The findings indicate that collaboration between the prison, vendors, and inmates is relatively effective, although challenges remain, such as suboptimal coordination and limited resources. The collaboration has had a positive impact on improving inmates’ skills, increasing land productivity, and contributing to food supply. The study recommends strengthening synergy among stakeholders and enhancing support from the government and private sector to improve the development system and ensure the success of food security programs within correctional facilities.